Microhardness of dual-polymerized resin cement around a translucent fiber post in the intraradicular environment - Özcan, Mutlu; Zamboni, Sandra [UNESP]; Valandro, Felipe [UNESP]; Bottino, Marco [UNESP]; Bagis, Bora (Wolters Kluwer, 2011)
Aim: In this study, we evaluated the effect of photopolymerization on Vickers microhardness of dual-polymerized resin cement at three locations when a translucent quartz fiber post was used. Materials and Methods: Single-rooted bovine teeth received quartz fiber post systems (length: 12 mm) using a dual-polymerized resin cement. In Group 1, the posts were cemented but not photopolymerized, and in Group 2, the posts were both cemented and photopolymerized. After cementation, approximately 1.5-mm thick sections were obtained (two cervical, two middle, and two apical) for regional microhardness evaluations. Statistical Analysis: Statistical analyses were performed using the SPSS software (ver. 11.0 for Windows; SPSS, Inc., Chicago, IL, USA). Microhardness (kg/mm 2 ) data were submitted to two-way analysis of variance (two-way ANOVA) and repeated measures with microhardness values as the dependent variable and polymerization status (two levels: with and without) and root region (three levels: cervical, middle, and apical) as independent variables. Multiple comparisons were made using Dunnett's T3 post-hoc test. P values of <0.05 were considered to indicate statistical significance in all tests. Results: Photopolymerization did not significantly change the microhardness values when compared with no photopolymerization. Microhardness values also showed no significant difference between the three regions in the root canals in both groups. Conclusions: The mode of polymerization of the cement tested in combination with the translucent quartz fiber post system did not affect the microhardness of the cement at the cervical, middle, or apical regions of the root.
Keywords: Fiber posts; microhardness; photopolymerization; resin cement